2020
DOI: 10.1371/journal.pone.0227358
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of liver fibrosis in non-viral liver diseases using acoustic radiation force impulse elastography: A systematic review and meta-analysis

Abstract: BackgroundAcoustic radiation force impulse (ARFI) imaging is an ultrasound-based elastography method that has been studied in the staging of hepatic fibrosis, especially in chronic hepatitis. However, the diagnostic accuracy of ARFI in non-viral hepatopathies, such as autoimmune hepatitis and non-alcoholic fatty liver disease, has not been systematically determined. OPEN ACCESSCitation: Lin Y, Li H, Jin C, Wang H, Jiang B (2020) The diagnostic accuracy of liver fibrosis in non-viral liver diseases using acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 56 publications
2
33
0
3
Order By: Relevance
“…Since 2015 there have been numerous publications and meta-analyses regarding the accuracy of pSWE and 2D-SWE for liver fibrosis staging in comparison to liver biopsy. In addition to the data already available for HCV and HBV, suggesting accuracies similar to TE, a metaanalysis on the performance of pSWE in 29 studies in patients with chronic liver disease due to non-viral aetiologies 253 showed an AUROC of 0.94 for advanced fibrosis and cirrhosis.…”
Section: Compensated Advanced Chronic Liver Disease and Portal Hypertensionmentioning
confidence: 90%
“…Since 2015 there have been numerous publications and meta-analyses regarding the accuracy of pSWE and 2D-SWE for liver fibrosis staging in comparison to liver biopsy. In addition to the data already available for HCV and HBV, suggesting accuracies similar to TE, a metaanalysis on the performance of pSWE in 29 studies in patients with chronic liver disease due to non-viral aetiologies 253 showed an AUROC of 0.94 for advanced fibrosis and cirrhosis.…”
Section: Compensated Advanced Chronic Liver Disease and Portal Hypertensionmentioning
confidence: 90%
“…However, a recent systematic review and meta-analysis suggests that ARFI is an acceptable diagnostic tool in staging hepatic fibrosis of non-viral origin, in particular in the case of severe fibrosis (F ≥3). 57 …”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis, however, indicated ARFI as a suitable tool in staging liver fibrosis of non-viral origin, mainly in the case of severe fibrosis. 57 By contrast, over- or underestimation of the anatomo-pathological results is also possible following liver histology. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…The examiner is able to use grayscale ultrasound imaging to locate a small region of interest (ROI) in the right hepatic lobe, avoiding large vessels and the gallbladder. The diagnostic performance of SWE, as reported in a meta-analysis, is demonstrated in Table 1 [ 12 , 13 ]. The advantage of point shear wave elastography is that it can be performed under B-mode ultrasound, so tumors and large vessels can be avoided.…”
Section: Noninvasive Imaging Techniquesmentioning
confidence: 99%